2012
DOI: 10.1021/jf303153d
|View full text |Cite
|
Sign up to set email alerts
|

Addition of β-Lactoglobulin Produces Water-Soluble Shikonin

Abstract: Shikonin and its ester derivatives belong to a group of secondary metabolites with a wide array of beneficial effects on human health. However, shikonin is principally used in oil-based preparations due to the low solubility of the pigment in aqueous media, and the positive properties of shikonin are not exploited to their full potential. Such low aqueous solubility often results in poor bioavailability, makes shikonin undesirable for oral administration, and restricts its broadened use in the food and pharmac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 46 publications
0
23
0
2
Order By: Relevance
“…Unfortunately, studies on the toxicity of this molecule in different species and with different administration routes are still missing and should be carried out. Due to its high lipophilicity, shikonin is generally used in creams and ointments, that is, oil-based preparations; indeed, its insolubility in water is usually the cause of its low bioavailability [3]. Moreover, shikonin and its derivatives are also thermolabile and prone to oxidation and polymerization [3][4][5].…”
Section: The Pharmacokinetics and Bioavailability Of Shikoninmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, studies on the toxicity of this molecule in different species and with different administration routes are still missing and should be carried out. Due to its high lipophilicity, shikonin is generally used in creams and ointments, that is, oil-based preparations; indeed, its insolubility in water is usually the cause of its low bioavailability [3]. Moreover, shikonin and its derivatives are also thermolabile and prone to oxidation and polymerization [3][4][5].…”
Section: The Pharmacokinetics and Bioavailability Of Shikoninmentioning
confidence: 99%
“…Due to its high lipophilicity, shikonin is generally used in creams and ointments, that is, oil-based preparations; indeed, its insolubility in water is usually the cause of its low bioavailability [3]. Moreover, shikonin and its derivatives are also thermolabile and prone to oxidation and polymerization [3][4][5]. One study using 3 H-shikonin in mice showed that shikonin was rapidly absorbed after oral and intramuscular administration, with a half-life in plasma of 8.79 h and a distribution volume of 8.91 L/kg.…”
Section: The Pharmacokinetics and Bioavailability Of Shikoninmentioning
confidence: 99%
“…We suppose that the reaction mechanism could be based on nucleophilic addition, where thiol of Cys121 or Cys119 attacks the electrophilic ethylidene C3-C3' bond of PCB with formation of a thioether bond, similarly to formation of thioether between BLG Cys121 and shikonin (Albreht, et al, 2012). According to all obtained results, we hypothesize that initially there is fast formation of non-covalent BLG-PCB complexes, with PCB binding preferentially in the calyx.…”
Section: Molecular Docking Reveals the Binding Of Pcb In The Calyx Ofmentioning
confidence: 61%
“…were identified (Albreht, Vovk, & Simonovska, 2012). Therefore, SMD simulation was used to simulate disulfide interchange between Cys121 and Cys119.…”
Section: Molecular Docking Reveals the Binding Of Pcb In The Calyx Ofmentioning
confidence: 99%
“…However, the therapeutic efficacy of shikonin is somewhat limited due to poor aqueous solubility and extensive first-pass metabolism, which are similar to those of many other chemotherapeutic drugs. 15,16 Thus, designing new formulations, which can obviously increase shikonin solubility and decrease its toxicity to normal tissue, is highly desired in clinics.…”
Section: Introductionmentioning
confidence: 99%